Enhanced photodynamic effect of a natural anthraquinone on Candida tropicalis biofilms using a stepwise irradiation strategy - Marioni, Juliana (2024)
BackgroundAntimicrobial Photodynamic Therapy (aPDT) has demonstrated effectiveness against various Candida biofilms, typical resistant to conventional treatments. Some strategies have shown to enhance the photoactivity of some photosensitizers (PS), such as the use of a multiple irradiation scheme or the combination with drugs that improve the penetration of the PS through the microbial membrane.PurposeHaving demonstrated the photodynamic antibiofilm activity of some natural anthraquinones (AQs), we selected rubiadin 1-methyl ether (R-1ME) that showed a low photo-reduction percentage (%R) on the biofilm mass, with the aim to improve its effect.Study DesignExperimental in vitro photo-stimulation protocols have been developed, which include successive light exposures and the combination of this AQ with a commonly used antifungal such as Amphotericin B (AmB).MethodsThe biofilms reduction was quantified by Crystal Violet staining. Reactive oxygen and nitrosative species were observed as action mechanism, alongside an assessment of antioxidant response through superoxide dismutase enzyme activation and total antioxidant system capacity.ResultsApplying R-1ME to C. tropicalis biofilms with sequential 15-min irradiation sessions at varied incubation intervals (0, 3, 6, 24, 27, and 30 h) yielded a substantial photo-reduction (62.9 %R) on biofilm mass, even halving the bioactive concentration of R-1ME. Moreover, combining R-1ME with AmB under this irradiation pattern produced an even greater impact (82 %R) at concentrations below the Minimal Inhibitory Concentration. Evident redox imbalances in the biofilm were linked to this photosensitized activity.ConclusionsA new strategy was found to improve the activity of a natural PS on fungal biofilms, by combining it with antifungal drugs, under a staged irradiation scheme, which, in turn, required low doses of the PS and the antifungal to achieve this improved photo-reduction.